Playful technologies for adolescents used by health professionals: an integrative review - Marta Maria Francisco; Eliane Maria Ribeiro de Vasconcelos; Maria Gorete Lucena de Vasconcelos; Maria Auxiliadora Soares Padilha; Ednaldo Cavalcante de Araujo; Jones Sidnei Barbosa de Oliveira (Universidade Federal de Santa Maria, 2020)
Objective: identify the playful technologies used by health professionals for adolescents. Method: Integrative review. The databases were: Lilacs, Bdenf, Cinahl, Adolec, Cuiden and Pepsic; SciELO, Cochrane library and Medline / Pubmed. The descriptors extracted from DeCS and MESH, being the final sample of five original articles. Search period from November 2017 to January 2018. Results: the articles featured a digital game, a straight chat game, questions and answers, the culture circle, a domino and a card game. They were between the years 2009 to 2018. The level of evidence six with methodological rigor category A. Final considerations: despite the articles being aimed at teenagers, there is still a need to develop new playful technologies by health professionals, covering other diseases for this audience, these being protagonists of the teaching-learning process, but also multipliers of health education actions.